2021
DOI: 10.1109/maes.2021.3052318
|View full text |Cite
|
Sign up to set email alerts
|

Flight Trial Demonstration of Secure GBAS via the L-band Digital Aeronautical Communications System (LDACS)

Abstract: The Ground Based Augmentation System (GBAS) is the cornerstone for enabling automated landings without the Instrument Landing System (ILS). Currently GBAS is evolving to GAST-D for CAT III landings. This extends GBAS via the use of multiple frequencies (L1/L2 and L5) and the use of multiple global navigation satellite system constellations. GBAS requires correction data to be broadcast to aircraft. This is currently done with the VHF Data Broadcast (VDB) datalink. However, VDB has several known shortcomings: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…GBAS over LDACS was first demonstrated in the MICONAV project as reported by Mäurer et al [12] and Bellido et al [3]. The main purpose of the GBAS over LDACS experiment was to demonstrate the ability of LDACS to provide a secure, broadband datalink for GBAS.…”
Section: Mäurer's Demonstration Of Gbas Over Ldacsmentioning
confidence: 99%
See 4 more Smart Citations
“…GBAS over LDACS was first demonstrated in the MICONAV project as reported by Mäurer et al [12] and Bellido et al [3]. The main purpose of the GBAS over LDACS experiment was to demonstrate the ability of LDACS to provide a secure, broadband datalink for GBAS.…”
Section: Mäurer's Demonstration Of Gbas Over Ldacsmentioning
confidence: 99%
“…The TESLA protocol has several requirements to work: Sender and receivers have to be loosely time synchronized; they have to have previously agreed upon key derivation, MAC tag generation, and verification algorithms; and every new participant has to receive the TESLA parameters in an authentic manner. [13] Analysis of Mäurer's results [12] indicated that the configuration of the TESLA protocol has a profound impact on the overall performance of secure GBAS over LDACS. The main TESLA parameters, that are relevant in the context of this paper are: the interval time T int , the key disclosure delay d, and the key k i for generating a MAC of a message m to be sent in interval i.…”
Section: A Background On Teslamentioning
confidence: 99%
See 3 more Smart Citations